Gender and geography : developments in the United Kingdom 1980-2006 - Jo Little (Belgeo)
This paper outlines the progress of feminist geography in the UK over the past 25 years, drawing on just some of the rich texts that have been produced. It charts the development of the sub-discipline through the key theoretical shifts. Within this discussion it pays particular attention to recent developments in feminist geography in the UK. It examines the ways in which geographers have adopted the concept of gender identity enabling them to explore more effectively the differing experiences between and within genders. The paper also shows how work on sexuality and the body has had a growing influence on the study of gender and on the construction and experience of identity. Using the example of rural geography, the paper goes on to explore how feminist approaches have influenced a particular sub-area of geography over the past 30 years. The paper ends by asserting that while there is much to celebrate in the development of feminist geography in the UK, there is still a need for a continued emphasis on gender equality.